Web application to measure level of addictive game - Latubessy, Anastasya; Jazuli, Ahmad (International Journal of Engineering and Technology, 2018)
Game becomes very popular within all ages. The intensity of someone playing games can influence the behavior of that person. World Health Organization (WHO) is classifying gaming disorder as an addictive behavior disorder. According to psychologists, there are six types of game addiction behavior, such as, Salience, Euphoria, Conflict, Tolerance, Withdrawal, and the last is Relapse and Reinstatement. A person is said to be addicted to the game if it meets at least three of the six types of behavior that exist. The six types of game addiction behavior then modeled using backward chaining algorithm. After that, the model was implemented into the system. Thus this research re-sult a web application to identify game addiction. Now we can measure how many people are affected using this web application.
Keywords: Web Application; Game Addiction; Backward Chaining; Algorithm.